Risk Factors for Traumatic Brain Injuries During Falls in Older Persons. Issue 6 (November 2015) - Hwang, Hei-Fen; Cheng, Chui-Hsuan; Chien, Ding-Kuo; Yu, Wen-Yu; Lin, Mau-Roung
Abstract : Objective: To identify risk factors for traumatic brain injuries (TBIs) during falls in older Taiwanese people. Participants: Case patients consisted of 113 patients aged 60 years or older with a moderate/severe TBI due to a fall. Two control groups: (1) 339 older patients with a soft-tissue injury; and (2) 113 with a mild-TBI due to a fall. Proxies were required to provide information for a considerable number of patients. Design: Matched case-control study. Settings: The emergency departments of 3 general hospitals. Measures: Sociodemographic, lifestyle behavior, chronic condition, medication use, functional abilities, and fall-related characteristics. Results: When patients with a soft-tissue injury were assigned to the control group, men were 2.06-fold more likely to have a moderate/severe TBI than women. Subjects who took antiarrhythmics within 4 hours of a fall were 2.59-fold more likely to have a moderate/severe TBI than those who took none. Subjects who were negotiating stairs and getting in/out of the bed/chair were 3.12-fold and 2.97-fold, respectively, more likely to have a moderate/severe TBI than those who fell while walking. Falling backward and sideways was 4.07-fold and 2.30-fold, respectively, more likely to cause a moderate/severe TBI than falling forward. When patients with a mild-TBI were assigned to the control group, results were similar, with the exception that the effect of antiarrhythmic use became nonsignificant and subjects who took 2 or more medications were 3.07-fold more likely to have a moderate/severe TBI than those who took none. Conclusion: Avoiding a head impact during a backward or sideways fall, reducing unnecessary use of polypharmacy and antiarrhythmics, and maintaining safety during stair negotiation and bed/chair transfer may protect an elderly person from a severe brain injury.